Plant Species Diversity and the Interconnection of Ritual Beliefs and Local Horticulture in Heet Sip Song Ceremonies, Roi Et Province, Northeastern Thailand - Piyaporn Saensouk; Surapon Saensouk; Thawatphong Boonma; Areerat Ragsasilp; Auemporn Junsongduang; Khamfa Chanthavongsa; Tammanoon Jitpromma (Horticulturae)
This study explores the ethnobotanical significance of plant species used in the Heet Sip Song (Twelve Monthly Merit-Making) ceremonies in Roi Et Province, Northeastern Thailand. A total of 80 plant species across 73 genera and 42 families were documented. The findings reveal that plants play multifaceted roles in ceremonial life, serving both symbolic and practical purposes rooted in spiritual belief systems and seasonal agricultural cycles. Quantitative analyses using Cultural Significance Index (CSI), Species Use Value (SUV), Genera Use Value (GUV), and Relative Frequency of Citation (RFC) highlighted the prominence of key species such as Oryza sativa, Musa acuminata, and Saccharum officinarum in ritual contexts. While staple crops dominate in frequency and cultural value, less commonly cited wild species fulfill specialized functions, reflecting deep local ecological knowledge. The integration of ritual and plant use promotes biodiversity conservation by maintaining plant populations and reinforcing sustainable harvesting practices. These results emphasize the vital role of traditional knowledge in conserving both biological and cultural diversity. As environmental pressures increase, this study underscores the importance of supporting community-led conservation efforts that honor indigenous practices and their contributions to ecological resilience.